The Validity of Transfer of Receivables (Cessie) from the Cessioner I Buyer to the Cessioner II Buyer in Review from the Civil Code - Ning Sriati; Noor Fatimah Mediawati (Indonesian Journal of Law and Economics Review, 2021)
The purpose of this study is to analyze the validity of a transfer of receivables (cessie) and to find out whether there is legal protection against Cessioner II. This research was conducted by reviewing Article 613 of the Civil Code concerning the Transfer of Receivables and Article 1320 of the Engagement. Using the statute approach as the type of research. The conclusion of this study states that the validity of the cessie is valid because there was a previous credit agreement between Bank BTN (cedent) and the debtor involving Cessioners I and II in accordance with the contents of Articles 613 and 1320 of the Civil Code. The existence of this legitimacy makes Cessioner II as the creditor the latest to receive legal protection, in the event of a default from the debtor.